Vestibular end organ injury induced by middle ear treatment with ferric chloride in rats. (February 2017) - Lee, JH; Kim, MS; Park, BR
Sensorineural hearing loss, ataxia, pyramidal signs, and vestibular deficits characterize superficial siderosis of the central nervous system. This study investigated changes in vestibular function, free radical formation, and phosphorylated cJun expression in the vestibular end organs after middle ear treatment with a ferric chloride (FeCl3 ) solution. A single injection of 70% FeCl3 solution into the unilateral middle ear cavity caused static vestibular symptoms, such as spontaneous nystagmus and head tilt. Asymmetric expression of c-Fos protein was observed in the bilateral vestibular nuclei and prepositus hypoglossal nuclei within 6 h after injection. Histopathologic examinations revealed partial hair cell loss, degeneration of the supporting stroma, and terminal deoxynucleotidyl transferase dUTP nick end labeling-positive cells in the neuroepithelial layer of the crista ampullaris in FeCl3 -treated animals. 5-(And-6)-chloromethyl-2′, 7′-dichlorodihydrofluorescein diacetate, acetyl ester and diaminofluorescein–2 diacetate fluorescence and immunoreactivity for nitrotyrosine increased markedly in the sensory neuroepithelial layer and nerve bundles of the crista ampullaris after 2 h. Strong immunoreactivity for phospho-cJun and cJun was observed in the type I hair cells of the crista ampullaris 120 h after injection. Thus, a single short-term treatment with a high concentration of FeCl3 in the unilateral middle ear cavity can induce activation of intracellular signals for cJun protein and oxidative stress through the formation of reactive oxygen species and nitric oxide in vestibular sensory receptors, resulting in vestibular dysfunction. These results suggest that activation of intracellular signals for cJun protein and oxidative stress may be a key component of the pathogenesis of vestibular deficits in patients with superficial siderosis.